Double strategies for reproducing multimodal puns in interlinguistic translation: An experimental research - Rebrii, Oleksandr; Frolova, Iryna; Rebrii, Inna (Lesya Ukrainka Eastern European National University, 2024)
The research is dedicated to exposing the specifics of translating multimodal puns based on the retrospective experiment. A multimodal pun is defined as a creolized/ polycoded formation substantiated by a specific type of ambiguity consisting of two inhomogeneous semiotic modes. The material for our research was provided by verbal-visual puns functioning as separate texts. Each multimodal pun results from intersemiotic translation when the signs of one semiotic system are transformed into the signs of another. For the vast majority of multimodal puns, verbal signs are interpreted into pictures, but the opposite cannot be excluded either. The role of the visual component is twofold. It can be creative when the picture is part of the ambiguity mechanism, or it can be amplifying when the picture accentuates the verbal wordplay, not participating directly in the creation of ambiguity. Hence, our first hypothesis is that multimodal puns with an amplifying visual component are a lesser challenge for translators than those with a creative one due to the absence of the necessity to coordinate verbal and visual modes in the target text. The research aims to identify the strategies of interlinguistic translation of multimodal puns and the factors that determine them, particularly the impact of the visual mode on the translator’s decision-making. Hence, our second hypothesis is that multimodal puns require double strategies that would allow to correlate the reproduction of the elements of two different semiotic systems. The analysis of the subjects’ translations, as well as their reports received in the course of the delayed retrospective experiment, confirmed both hypotheses.
Keywords: interlinguistic translation; intersemiotic translation; multimodal pun; retrospective experiment; translation strategy; verbal mode; visual mode